The challenges of establishing partnership policing in Soshanguve township, South Africa: research - Mabunda, Dumisani Quiet (Acta criminologica, 2018)
This article investigates factors that inhibit the implementation of partnership policing in Soshanguve Township (north of Pretoria) in South Africa. In this research, 45 participants were interviewed in a series of focus-group interviews. These participants ranged from members of the South African Police Service to members of the community in the area. Furthermore, the article examines what challenges were encountered in the implementation of partnership policing in the area, and to what extent the local police met these challenges. The results can assist policy makers and police management on how to improve policing activities and implementation efforts. Although the study focused on Soshanguve Township, its findings may have implications for many policing areas in South Africa that are faced with similar challenges in the implementation of partnership policing. The results indicated that community members tend to disagree on whether the police understand their role in or are confused about the partnership policing strategy and principles. The research revealed that much uncertainty in Soshanguve still surrounds the proper implementation of community policing in this township. Due to the challenges, the partnership policing strategy in the township, at the time of the research study, was yet to produce the expected results on crime prevention.